Insulting women against men and defaming their stature in the light of contemporary social interpretation= تشنيع المرأة على الرجل والطعن في قوامته في ضوء التفسير الاجتماعي المعاصر - Almeri, Halah; Khaled, Nashwan Abdo (Privilege on Behalf of Karabuk University Faculty of Islamic Sciences Murat ŞİMŞEK, 2021)
يهدف هذا البحث إلى التعريف بقضية تشنيع المرأة على الرجل والطعن في قوامته، ودراسة هذه القضية من الناحية الاجتماعية في ضوء القرآن الكريم، والبحث في سبب هذه القوامة التي جعلها الشارع خاصة للرجل دون المرأة، وحقيقة هذه القوامة وحدودها، ومناقشة الفهم الخاطيء للقوامة في الفكر النسوي ومايشابهه من مغالطات وشبهات أثيرت من أعداء الإسلام، والذي يهدف إلى تشويه صورة الإسلام أمام المجتمعات الغربية والإسلامية كذلك والرد عليها بالأدلة الشرعية النقلية، والعقلية بما يوافق الفطر السليمة، واستخدم البحث المنهج التحليلي لتحليل هذه القضية والرد على الشبهات الواردة فيها، والمنهج الاستقرائي في دراسة المفاهيم والمصطلحات، مستدلة بأقوال وتفاسير العلماء خصوصًا المتأخرين من أصحاب مدرسة التفسير الاجتماعي، ثم خلصت الدراسة إلى نتائج من أهمها: أن الإسلام كرّم المرأة، ورفع من شأنها، وكفل لها الحرية المنضبطة بضوابط شرعية، القوامة الزوجية إنما هي للرجل، وليست للمرأة بنص القرآن الكريم، وأن وظيفة القوامة لا تعني تسلط الرجل، كما لا تعني سلب حقوق المرأة أو تهميش رأيها ووجودها في الحياة. This research aims to discuss the issue of women’s defamation of men’s reputation and objecting their stature, study this issue from a social point of view in the light of the Holy Qur’an, and research the reason for the responsibility that the legislator has assigned to men without women, the reality of responsibility and its limits. It also clarified the misunderstanding of the responsibility in feminist thought and the similar fallacies and suspicions raised by the enemies of Islam, which aims to distort the image of Islam in front of Western and Islamic societies and respond to it with legal, transmission, and mental evidence in accordance with common sense, and the analytical method was used to analyze this issue and respond to the suspicions received In it, as well as the inductive approach in studying concepts and terminology, inferred by the sayings and interpretations of scholars, especially the later owners of the school of social interpretation, then the study concluded with results, the most important of which are: Islam honored the woman, raised her status, and guaranteed her freedom that was regulated by legal regulations, but the marital responsibility is for the man, not for the woman according to the text of the Holy Qur’an, and that the